The Rationality of Student Political Choices in the 2024 Presidential Election - Nursi, Muhammad; Pebriyenni, Pebriyenni; Darwianis, Darwianis; Muslim, Muslim; Yuza, Arlina (ARISTO, 2024)
Students are one of the important social segments that are affected and have an impact on the 2024 Presidential General Election (Pilpres). Therefore, this research aims to describe the rationality of students' political choices between rational, primordial, pragmatic, and emotional preferences or types, as well as their comparison with each other. With a population of 6174 students of Hatta University, spread across 33 study programs in the Even Semester 2023-2024, namely with cluster data collection techniques and proportional random sampling, the research sample was 330 people (5.34%), using a questionnaire instrument. The results of this study show that in real and internal comparison, each type of student political choice between rational and non-rational (irrational) preferences/types is contrasting but weak, namely 60.1% compared to 11.9%, primordial type 55.6% and non-primordial type 15.3%, pragmatic type 59.8% and non-pragmatic type 15.3%, while emotional type is 60.1% and non-emotional type 11.9%. Externally and in real terms, there is no dominant (weak) difference. However, the negative preferences of the primordial and emotional types were still more prominent, namely 55.6% and 60.1% (both less strong), so that the average difference in percentage with non-primordialism and non-emotional was 44.25% (less strong)